THE EARLY HOME ENVIRONMENT OF LATINO BOYS AND THEIR PEERS: A DEVELOPMENTAL PERSPECTIVE. Issue 1 (27th December 2016) - Cabrera, Natasha J.; Malin, Jenessa L.; Kuhns, Catherine; West, Jerry
ABSTRACT: Using a sample ( N = 5, 200) drawn from the Early Childhood Longitudinal Study‐Birth Cohort, we examined Latino boys' developmental profiles and their early home experiences from 9 months to kindergarten entry in comparison to their peers—Latina girls and White boys. We also examined how children's early home experiences related to outcomes at kindergarten entry and whether these varied by gender and ethnicity. Controlling for socioeconomic indicators, the largest mean group differences were between Latino and White boys, beginning at 24 months and persisting at kindergarten entry. There were modest differences between Latino boys and Latina girls on some outcomes, with boys showing an early and persistent advantage in math and girls showing a persistent advantage in social skills. Household resources and maternal and paternal investments in literacy activities were the strongest predictors of children's preacademic skills at kindergarten entry. Our model did not vary by gender or ethnicity, suggesting that the ingredients for learning are the same for all children.